Morrisons : equity valuation - Monteiro, Artur dos Santos (2019)
The following dissertation aims to evaluate Wm Morrison Supermarkets PLC, one of the biggest players in UK’s retail Industry. The company owns around 500 stores spread around the UK and is present in all the supply chain. The main objective is to determine the fair price per share of the company, on the 31st of December 2018. In order to accomplish it, the dissertation will rely on two different valuation methods: Discounted Cash Flow (using the Weighted Average Cost of Capital), and Relative Valuation. Moreover, a comparison between the dissertation findings and an Investment Bank report, issued by J.P. Morgan Cazenove, about Morrisons will be done, in which the difference between the assumptions used by both will be discussed. After the application of the DCF method, taking in account the author’s assumptions, it was concluded that Morrisons should have a share price of 306 GBX.